Ambivalence, Avoidance, and Appeal: Alliterative Aspects of Anglo Anthroponyms. (2nd July 2020) - Bush, Stephen J.
Abstract : In several countries, one of the most pronounced trends in contemporary baby naming is selecting a comparatively uncommon name. Nevertheless, although a well-documented phenomenon, studies of uncommon name use are often limited to forenames. This study analyses approximately 22 million full names from England and 1 million from Wales, given between 1838 and 2014. It addresses the hypothesis that, consistent with the contemporary desire to choose an uncommon name, alliterative names – uncommon by definition – would become increasingly popular. More broadly, this study charts the long-term trends in alliterative naming over time. In both England and Wales, this pattern is consistent with a random expectation for much of the 19 th century but declines significantly throughout the 20 th century to its lowest use in the 1970s. This trend reverses towards the end of the 20 th century, with alliterative naming becoming more common in contemporary records. These three aspects of alliterative name use are thematically referred to as 'ambivalence', 'avoidance' and 'appeal'; and may reflect changing attitudes towards alliterative naming. The relatively renewed appeal of alliterative names towards the end of the 20 th century complements previous research on the preponderance of uncommon names and the contemporary 'need for uniqueness' in naming.